Overview of The Infection Control Risk Assessment (ICRA) Implementation in Dental Practice at RSGM Unimus - Dwi Windu Kinanti Arti; Aulia Rizqi Niami; Retno Kusniati (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2023)
Infections present while undergoing treatment or obtained from health services are called Healthcare-Associated Infections (HAIs). The impact of this incident is the length of treatment and costs provided, increased morbidity, and can result in death. One of the many occupations in the world with the highest risk of infection transmission is health workers working in dentistry since most of human microbial pathogens originate from oral secretions. In contrast, these health workers require their proximity to the patient’s oropharynx. The increase in HAIs occurs due to the lack of application of infection control, so we need to assess this implementation. The Centers for Disease Control and Prevention (CDC), in 2016, issued standardized Infection Control Risk Assessment (ICRA) guidelines to assess the risk of infection in dental and oral health services. This research aims to describe ICRA in the dentist practice at RSGM Unimus. The type of research used was observational, with quantitative analysis methods and a descriptive research design. The results showed that overall, infection control at RSGM Unimus had a percentage of 82%, which was included in the low infection risk category. RSGM Unimus was good at implementing infection control programs.